Anxiety, Depression, and Stress on School-Aged Children and Adolescents in 2021: An Urgent Need for Comprehensive Intervention and Support - A. Romero; M. Petro; E. P. Ruiz (European Psychiatry, 2024)
Introduction In the year 2021, there was a notable increase in behaviors associated with anxiety, depression, and stress among school-aged children and adolescents, possibly attributed to the pervasive effects of social isolation and confinement measures.